Selection of urinary sediment miRNAs as specific biomarkers of IgA nephropathy - Duan, Zhi-Yu (Sci Rep, 2016)
The miRNAs in urinary sediment are easy to obtain, which provides a new approach to searching for non-invasive biomarkers of IgA nephropathy (IgAN). Compared with normal controls (n = 3), 214 different miRNAs in the urinary sediment of IgAN (n = 9) were found by miRNA chip assay. By quantitative PCR analysis, miR-25-3p, miR-144-3p and miR-486-5p were confirmed to be significantly higher in IgAN (n = 93) than in the normal group (n = 82) or disease control (n = 40). These three miRNAs had good specificity and sensitivity for the diagnosis of IgAN by receiver operating characteristic curve analysis, in which the AUC value of miR-486-5p was the largest at 0.935. Urinary sediment miR-25-3p, miR-144-3p and miR-486-5p were demonstrated to be mainly derived from urinary erythrocytes, which were separated by CD235a magnetic beads. The increased expression of urinary erythrocyte miRNAs in IgAN patients was not associated with those in the blood erythrocytes. In addition, urinary supernatant microvesicles of miR-144-3p and miR-486-5p in the IgAN group were also significantly increased. This study showed that the miR-25-3p, miR-144-3p and miR-486-5p in urinary sediment were mainly derived from urinary erythrocytes, which could be non-invasive candidate biomarkers for IgA nephropathy.